Stochastic structure determination for conformationally flexible heterogenous molecular clusters: Application to ionic liquids. Issue 30 (26th August 2013) - Addicoat, Matthew A.; Fukuoka, Syou; Page, Alister J.; Irle, Stephan
<x xml:space="preserve">Abstract</x> We present a novel method that enables accurate and efficient computational determination of conformationally flexible clusters, "Kick3" This method uses stochastically generated structures in combination with fast quantum mechanical methods. We demonstrate the power of this method by elucidating the structure of ionic liquid (IL) ([xMIM+][ <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg3kg2xr80" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />NO3−])n</alternatives> clusters (x = E, B, D, n = 1–10, 15). Dispersion‐corrected, third‐order self‐consistent‐charge density‐functional tight‐binding (DFTB3) is shown to be a computationally efficient, yet reliable approximation to density functional theory for predicting and understanding IL structure and stability. The presented approach, therefore, enables the accurate and efficient screening of ILs with high potential toward practical applications, without recourse to more expensive quantum chemical methods. © 2013 Wiley Periodicals, Inc.